1995
DOI: 10.1149/1.2048478
|View full text |Cite
|
Sign up to set email alerts
|

Application of Measurement Models to Impedance Spectroscopy: II . Determination of the Stochastic Contribution to the Error Structure

Abstract: Development of appropriate models for the interpretation of impedance spectra in terms of physical properties requires, in addition to insight into the chemistry and physics of the system, an understanding of the measurement error structure. The time-varying character of electrochemical systems has prevented experimental determination of the stochastic contribution to the error structure. A method is presented by which the stochastic contribution to the error structure can be determined, even for systems for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 6 publications
2
94
1
3
Order By: Relevance
“…The expression used for σ corresponds to an assumption that the standard deviation for the impedance measurement was equal to one percent of the modulus. An improved regression could be obtained by experimental determination of the error structure using, for example, the measurement model concept promoted by Agarwal et al 25 This would not have a significant influence on the results reported here because, to a first approximation, the errors obtained under potentiostatic modulation are proportional to the modulus of the impedance. As the weight applied was the same for all regressions, changes in the value of χ 2 provide a good indication of the comparative quality of the fit.…”
Section: Methodsmentioning
confidence: 88%
“…The expression used for σ corresponds to an assumption that the standard deviation for the impedance measurement was equal to one percent of the modulus. An improved regression could be obtained by experimental determination of the error structure using, for example, the measurement model concept promoted by Agarwal et al 25 This would not have a significant influence on the results reported here because, to a first approximation, the errors obtained under potentiostatic modulation are proportional to the modulus of the impedance. As the weight applied was the same for all regressions, changes in the value of χ 2 provide a good indication of the comparative quality of the fit.…”
Section: Methodsmentioning
confidence: 88%
“…Following the procedure described by Agarwal et al, 10,11 sequential Voigt elements were added to the model until the addition of an element did not improve the fit and one or more model parameters included zero within their 95.4 percent (2σ) confidence interval.…”
Section: The Approachesmentioning
confidence: 99%
“…From an experimental point of view, all the requirements for performing a global impedance measurement (i.e. linearity, stability, and causality) remain the same for LEIS, and the validity of the measurements can be checked using the Kramers-Kronig relationship directly or through use of the measurement model [52][53][54].…”
Section: Potential Difference Measurement and Spatial Resolutionmentioning
confidence: 99%